Effects of cellulose nanofibrils on the structure and properties of maleic anhydride crosslinked poly(vinyl alcohol) electrospun nanofibers - Braga, Cátia Sofia Neves (2019)
Nanofibers of poly(vinyl alcohol) (PVA) reinforced with cellulose nanofibrils (CNFs) and/or crosslinked with maleic anhydride (MA) were produced by electrospinning technique to compare the additivation effects of the polymeric matrix. The results suggested that the PVA mass fraction equal to 14%, CNFs volumetric fraction of 3% and maleic acid at the molar ratio 20:1 are the best proportions for renewable base fibres production. In this study, the best electrospinning parameters for membranes production were obtained at the applied voltage of 24 kV, needle tip-to-collector distance of 14.5 cm, feed rate of 0.3 mL h1 and using a plate collector. CNFs and MA additions allow to improve nanofiber thermal properties and resistance to water degradation, which result in an eco-friendlier, biocompatible and long-term biodegradable nanofiber mats with diameters of 74±33 nm for water filtration purposes.